Analysis and Quantification of Demand Flexibility for Resilient Distribution Networks: A Systematic Review - Mohamed Massaoudi; Katherine R. Davis; Khandaker Akramul Haque (IEEE Access)
Modern power systems face increasing operational challenges due to the integration of renewable energy sources (RESs) and evolving demand patterns. Demand flexibility (DF) has emerged as a transformative solution by dynamically adjusting electricity consumption to align with grid conditions. This review systematically investigates DF in distribution networks through three critical dimensions: quantification methodologies, regulatory frameworks, and techno-economic impacts. Advanced quantification methods, including time-varying elasticity models, alternating current (AC) multi-temporal optimal power flow simulations, and region-based flexibility quantification techniques, are examined to establish accurate measurement frameworks. The regulatory and market mechanisms promoting DF adoption are analyzed, emphasizing dynamic pricing schemes and performance-based incentives. The role of policy in overcoming barriers such as consumer resistance, data privacy concerns, and limited market access for aggregators is critically evaluated. The techno-economic impacts of DF integration reveal significant benefits in grid reliability and infrastructure investment deferral, while highlighting implementation challenges. Through a synthesis of cutting-edge methodologies, this review provides actionable insights for researchers, policymakers, and industry stakeholders advancing resilient, flexible distribution networks in the evolving energy landscape.